Surgically placed abdominal wall catheters on postoperative analgesia and outcomes after living liver donation. Issue 4 (12th March 2015) - Khan, James; Katz, Joel; Montbriand, Janice; Ladak, Salima; McCluskey, Stuart; Srinivas, Coimbatore; Ko, Raynauld; Grant, David; Bradbury, Ashleene; LeManach, Yannick; Clarke, Hance
<x xml:space="preserve">Abstract</x> Living donor liver resections are associated with significant postoperative pain. Epidural analgesia is the gold standard for postoperative pain management, although it is often refused or contraindicated. Surgically placed abdominal wall catheters (AWCs) are a novel pain modality that can potentially provide pain relief for those patients who are unable to receive an epidural. A retrospective review was performed at a single center. Patients were categorized according to their postoperative pain modality: intravenous (IV) patient‐controlled analgesia (PCA), AWCs with IV PCA, or patient‐controlled epidural analgesia (PCEA). Pain scores, opioid consumption, and outcomes were compared for the first 3 postoperative days. Propensity score matches (PSMs) were performed to adjust for covariates and to confirm the primary analysis. The AWC group had significantly lower mean morphine‐equivalent consumption on postoperative day 3 [18.1 mg, standard error (SE) = 3.1 versus 28.2 mg, SE = 3.0; P = 0.02] and mean cumulative morphine‐equivalent consumption (97.2 mg, SE = 7.2 versus 121.0 mg, SE = 9.1; P = 0.04) in comparison with the IV PCA group; the difference in cumulative‐morphine equivalent remained significant in the PSMs. AWC pain scores were higher than those in the PCEA group and were similar to the those in the IV PCA group. The AWC group had a lower incidence of pruritus and a shorter hospital stay in comparison with the PCEA group and had a lower incidence of sedation in comparison with both groups. Time to ambulation, nausea, and vomiting were comparable among all 3 groups. The PSMs confirmed all results except for a decrease in the length of stay in comparison with PCEA. AWCs may be an alternative to epidural analgesia after living donor liver resections. Randomized trials are needed to verify the benefits of AWCs, including the safety and adverse effects. Liver Transpl 21:478–486, 2015. © 2015 AASLD.